Sparse observations induce large biases in estimates of the global ocean CO2 sink: an ocean model subsampling experiment ... - Hauck, Judith; Nissen, Cara; Landschützer, Peter; Rödenbeck, Christian; Bushinsky, Seth; Olsen, Are (Zenodo, 2023)
Dataset underlying the analysis in Hauck et al., 2023: Sparse observations induce large biases in estimates of the global ocean CO 2 sink - an ocean model subsampling experiment, Philosophical Transactions A Surface ocean partial pressure of CO 2 (pCO 2 ) and air-sea CO 2 flux reconstructions, using two mapping methods (MPI-SOM-FFN, CarboScope) three different sampling masks: SOCAT, SOCAT+SOCCOM, IDEAL (based on bgcArgo, Roemmich et al., 2019). Also, all FESOM-REcoM output fields that were used in the reconstructions are provided. We further provide the three masks that were used for subsampling: SOCAT, SOCAT+SOCCOM, IDEAL (bgcArgo). ... : {"references": ["Hauck et al., 2023: Sparse observations induce large biases in estimates of the global ocean CO2 sink - an ocean model subsampling experiment, Phil. Trans. R. Soc. A 381: 20220063. https://doi.org/10.1098/rsta.2022.0063"]} ...